Asian American Spring Festival 1987 Flyer 03 (SJSU Asian American Studies Department, 2024)
Asian American Spring Festival Career Panel Flyer. This event was held on Thursday, March 26 from 2:30 PM – 4:30 PM in the Student Union, Guadalupe Room.